2017
DOI: 10.5539/jas.v9n9p1
|View full text |Cite
|
Sign up to set email alerts
|

Low Temperature Storage and in vitro Pollen Germination of Selected Spring Wheat Accessions

Abstract: The study was conducted to evaluate in vitro pollen germination of 50 spring wheat (Triticum aestivum L.) accessions at three storage temperatures (23 °C, 5 °C, and -20 °C). Germination of the mature pollen was measured right after harvest (0 time), and 24, 48, and 72 h after storage (HAS). Differences in fresh pollen germination between accessions were significant and ranged from 21.15% to 1.09%. Pollen germination was the lowest at 24 h at room temperature. The pollens of 24 wheat accessions (AAC Scotia, AW6… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
7
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 14 publications
2
7
2
Order By: Relevance
“…In contrast, our study found that spring wheat genotypes maintained 6-14% germination at 4 °C after six days of storage. The data analysis emphasized the significant impact of genotypes on pollen viability and germination rates, as well as their interactions with storage temperatures and durations, corroborating earlier findings (Baninasab et al, 2017).…”
Section: Discussionsupporting
confidence: 85%
See 3 more Smart Citations
“…In contrast, our study found that spring wheat genotypes maintained 6-14% germination at 4 °C after six days of storage. The data analysis emphasized the significant impact of genotypes on pollen viability and germination rates, as well as their interactions with storage temperatures and durations, corroborating earlier findings (Baninasab et al, 2017).…”
Section: Discussionsupporting
confidence: 85%
“…Our study highlighted that pollen viability and in vitro pollen germination were notably higher at 4 °C than at −20 °C and 22 °C across all selected spring wheat genotypes. In a prior study, spring wheat genotypes stored at 5 °C exhibited approximately 1.64% pollen germination after 24 h of storage but experienced a complete loss of viability, with 0.00% germination after 48 and 72 h (Baninasab et al, 2017). In contrast, our study found that spring wheat genotypes maintained 6-14% germination at 4 °C after six days of storage.…”
Section: Discussioncontrasting
confidence: 66%
See 2 more Smart Citations
“…Pollen preservation is crucial for breeding and genetic research [8]. Limited data exist on wheat pollen storage at low temperatures, with one study reporting preservation at 5 • C for one day [25]. Pollen life spans differ significantly between plant species, genotypes, and cultivars [26].…”
Section: Introductionmentioning
confidence: 99%